Digital Governance and Health Innovation for Strengthening Community Health Systems: A Cross-Sectional Study in Indonesia - Wa Ode Novi Angraeni; Jessy Andre Mangaya Takke; Muh Ihsan Kamaruddin (Edukasi Ilmiah Indonesia, 2026)
Introduction: Digital transformation has become an important strategy for strengthening community health systems and improving the effectiveness of primary healthcare services. Digital governance and health innovation can support better coordination, data management, and accessibility of health services. However, empirical evidence examining the role of digital governance and innovation in strengthening community health systems in developing countries remains limited. This study aimed to examine the relationship between digital governance, health innovation, and community health system strengthening in primary healthcare facilities in Indonesia. Research Methodology: This study employed a cross-sectional design conducted in primary healthcare facilities in Indonesia between January and April 2025. A total of 150 healthcare professionals and administrative staff participated in the study. Data were collected using a structured questionnaire assessing digital governance, health innovation, and community health system strengthening. Descriptive statistics were used to summarize respondent characteristics. Bivariate analysis and multivariate logistic regression were performed to examine associations between variables. Statistical significance was determined at p < 0.05 with 95% confidence intervals. Results: Among the 150 respondents, most participants reported experience using digital health systems (81.3%). Bivariate analysis showed that digital governance was significantly associated with community health system strengthening (p = 0.003). Health innovation also demonstrated a significant association with community health system strengthening (p = 0.005). Multivariate logistic regression analysis indicated that facilities with higher digital governance had greater odds of stronger community health system performance (AOR = 2.36; 95% CI: 1.29–4.31; p = 0.004). Similarly, higher levels of health innovation were associated with improved community health system indicators (AOR = 2.08; 95% CI: 1.14–3.77; p = 0.016). Conclusions: Digital governance and health innovation play significant roles in strengthening community health systems within primary healthcare settings. Strengthening digital governance frameworks, expanding digital health infrastructure, and enhancing digital competencies among healthcare workers may improve the effectiveness of community-based healthcare delivery. Future research should explore longitudinal approaches to better understand the long-term impact of digital transformation on health system performance.